Electronic Simulator of the PLATO Satellite Imaging System - Ferrão,Rafael Corsi (2012)
Abstract: This paper described an architecture that is able to emulate the behavior of the imaging transfer system proposed for the PLATO satellite - PLAnetary transits and oscillations of stars. It was conceived to accurately represent flight operation as to validate the satellite digital processing unit on its development phase. Details related to the mission, its architecture, and the implementation technical details are presented in this article.